Comparative Analysis Among Different Species Reveals That the Androgen Receptor Regulates Chicken Follicle Selection Through Species-Specific Genes Related to Follicle Development - Huang, Ying; Luo, Wei; Luo, Xuliang; Wu, Xiaohui; Li, Jinqiu; Sun, Yan; Tang, Shuixin; Cao, Jianhua; Gong, Yanzhang (Frontiers in Genetics, 2022)
The differences in reproductive processes at the molecular level between viviparous and oviparous animals are evident, and the site in the ovary that synthesizes sex hormones (androgens and oestrogens) and the trends for enriching sex hormones during follicle development in chickens are different from those in mammals, suggesting that the effect of sex hormones on follicle development in chickens is probably different from that in viviparous animals. To explore the specific role of androgen receptors (ARs) on chicken follicular development, we matched the correspondence of follicular development stages among chickens, humans, cows and identified chicken-specific genes related to follicle development (GAL-SPGs) by comparing follicle development-related genes and their biological functions among species (chickens, humans, and cows). A comparison of the core transcription factor regulatory network of granulosa cells (or ovaries) based on super-enhancers among species (chicken, human, and mouse) revealed that AR is a core transcriptional regulator specific to chickens. In vivo experiments showed that inhibition of AR significantly reduced the number of syf (selected stage follicles) in chickens and decreased the expression of GAL-SPGs in F5 follicles, while in vitro experiments showed that inhibition of AR expression in chicken granulosa cells (GCs) significantly down-regulated the expression levels of GAL-SPGs, indicating that AR could regulate follicle selection through chicken-specific genes related to follicle development. A comparison among species (77 vertebrates) of the conserved genomic regions, where chicken super-enhancers are located, revealed that the chicken AR super-enhancer region is conserved in birds, suggesting that the role of AR in follicle selection maybe widespread in birds. In summary, we found that AR can regulate follicle selection through chicken-specific genes related to follicle development, which also emphasizes the important role of AR in follicle selection in chickens and provides a new perspective for understanding the unique process of follicle development in chickens. Our study will contribute to the application of androgens to the control of egg production in chickens and suggests that researchers can delve into the mechanisms of follicle development in birds based on androgen/androgen receptors.